Can endogenously chosen institutions mitigate the free-rider problem and reduce perverse punishment? - Arhan Ertan; Talbot Page; Louis Putterman (Brown University, Department of Economics, 2005)
Previous experiments on public goods dilemmas have found that the opportunity to punish leads to higher contributions and reduces the free rider problem; however, a substantial amount of punishment is targeted on high contributors. In the experiment reported here, subjects are given the opportunity to vote on rules governing punishment. We found that, from their first opportunity to vote, no group ever allowed punishment of high contributors, most groups eventually voted to allow punishment of low contributors, and a minority of groups never allowed any form of punishment. Groups allowing punishment of low but not high contributors had significantly higher efficiency and contributions than comparison groups with unrestricted punishment.
Keywords: C91; C92; D71; H41; 330; Public goods; collective action; punishment; voting; institutions; Öffentliches Gut; Trittbrettfahrerverhalten; Test; Theorie